Determinants of Depressive Symptoms, Quality of Life, Subjective Health Status and Physical Limitation in Patients with Systemic Sclerosis - Stefanie Heyne; Eva Haufe; Stefan Beissert; Jochen Schmitt; Claudia Günther (Medical Journals Sweden, 2023)
Systemic sclerosis is a progressive connective tissue disease for which there is limited knowledge about physical limitations, quality of life and depression. The aim of this study was to assess these parameters during the disease process of systemic sclerosis, in a cross- sectional study of 79 patients and a longitudinal study of 33 patients over 10 years. Medical data were collected by physicians' questionnaires and sociodemographic data, pain, physical limitation, quality of life, subjective health status, risk of depressive symptoms by patients' questionnaires. Data analysis was descriptive and exploratory. Cross-tabulations, χ2 test and Student's t-test were used for calculations, Pearson's correlation to measure dependencies, and logistic regression analyses for categorized parameters. The cross-sectional analysis of 79 patients with systemic sclerosis (81% female, mean ± standard deviation age 61.5 ± 12.6 years) demonstrated a higher rate of patients with risk of depressive symptoms (42.3%) higher physical limitations, lower quality of life, and subjective health status than reference values for the general German population. Moderate to strong correlations between disease-related physical limitation, quality of life, subjective health status, risk of depressive symptoms and pain were detected (correlation according to Pearson -0.459 to -0.638, p < 0.001). Longitudinal analysis revealed a significant increase in disease activity, pain, physical limitation and risk of depressive symptoms (p < 0.001) during the disease process. This study demonstrates that nearly half of patients with systemic sclerosis probably experience depressive symptoms. The rate of patients with risk of depressive symptoms, pain and physical limitations increased during the systemic sclerosis disease process. Health-related quality of life and state of health declined, indicating the need for better interdisciplinary care for patients with systemic sclerosis.